Tight times - Patindol, Jeanette C.; Bumatay, Sergio T., III (Quezon City Adarna House, Inc., 2007)
"These are tight times so we've got to be tough. They have less food to eat, less things to use, less places to go. What does a family do when faced with tight times? Find out how less can be more."
"A book in 2 languages." -- Cover.
This book is recommended for children ages 10 and above.
Text in English and Filipino.
PBBY-Salanga Prize, PBBY-Alcala Prize 2007 Grand Prize Winner.
Keywords: Children's stories, Philippine (English); Children's stories, Filipino